2012
DOI: 10.1002/rra.2615
|View full text |Cite
|
Sign up to set email alerts
|

Long Profile Responses of Alpine Braided Rivers in Se France

Abstract: Channel elevation change since the early 20th century was characterized for 31 alpine braided river reaches (total length of 129 km), representing about 20% of the braided river network length in SE France. Present‐day long profiles were surveyed in the field and compared with historical profiles measured between 1894 and 1930. Forty‐four cross sections of active channels including terrace boundaries were also surveyed to study morphological signatures of braided channels characterized by different channel res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 43 publications
2
57
0
Order By: Relevance
“…Western reaches have a lower slope and altitude values (types 1 and 2) compared to eastern reaches (types 4 and 5 and in part 3).Eastern reaches are strongly influenced by higher activity in terms of sediment delivery. They display higher W* values and a widening pattern, and some of these reaches are also aggraded (Liébault et al ., ). This may also contribute to the temporal gap in vegetation development, for a similar flood history.Regional climatic differences reinforce the west–east trend.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Western reaches have a lower slope and altitude values (types 1 and 2) compared to eastern reaches (types 4 and 5 and in part 3).Eastern reaches are strongly influenced by higher activity in terms of sediment delivery. They display higher W* values and a widening pattern, and some of these reaches are also aggraded (Liébault et al ., ). This may also contribute to the temporal gap in vegetation development, for a similar flood history.Regional climatic differences reinforce the west–east trend.…”
Section: Discussionmentioning
confidence: 97%
“…Liébault et al . () showed that for braided reaches locally affected by gravel mining, the channel readjustment has not been observed in all reaches concerned right after the end of mining activities in the 1990s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of geomorphic field surveys was carried out between 2006 and 2007 along the entire study reach, both validating and extending bibliographic information on past bed-elevation changes and present trends of vertical adjustments. Field evidence mainly included the differences in elevation between homologous geomorphic surfaces, such as: (1) between a low terrace identified as being a floodplain from past aerial photographs or other sources and the present active floodplain (Rinaldi 2003); (2) between wooded terraces deriving from abandoned channel surfaces and the top of active channel bars (Liébault et al 2013);and (3) between the top of a gravel lens visible on an eroding bank and the top of gravel in the present bed.…”
Section: Channel Morphology and Changesmentioning
confidence: 99%
“…It is worth emphasising, though, that RS data will never substitute the wide range of data sources that currently contribute to the accurate assessment of current river behaviour, geomorphological sensitivity and the evaluation of future trajectories (Simon and Rinaldi 2006;Liébault et al 2013;Grabowski et al 2014). Expert interpretations, field surveys and historical analysis will remain important ways of reading the landscape (Brierley et al 2013), but RS data will support and corroborate conclusions drawn from these sources.…”
Section: Resultsmentioning
confidence: 99%